8.0% Efficient All‐Polymer Solar Cells with High Photovoltage of 1.1 V and Internal Quantum Efficiency near Unity. Issue 1 (11th September 2017) - Xu, Xiaofeng; Li, Zhaojun; Zhang, Wei; Meng, Xiangyi; Zou, Xianshao; Di Carlo Rasi, Dario; Ma, Wei; Yartsev, Arkady; Andersson, Mats R.; Janssen, René A. J.; Wang, Ergang
Abstract: In very recent years, growing efforts have been devoted to the development of all‐polymer solar cells (all‐PSCs). One of the advantages of all‐PSCs over the fullerene‐based PSCs is the versatile design of both donor and acceptor polymers which allows the optimization of energy levels to maximize the open‐circuit voltage ( V oc ). However, there is no successful example of all‐PSCs with both high V oc over 1 V and high power conversion efficiency (PCE) up to 8% reported so far. In this work, a combination of a donor polymer poly[4, 8‐bis(5‐(2‐octylthio)thiophen‐2‐yl)benzo[1, 2‐ b :4, 5‐ b′ ]dithiophene‐2, 6‐diyl‐ alt ‐(5‐(2‐ethylhexyl)‐4 H ‐thieno[3, 4‐ c ]pyrrole‐4, 6(5 H )‐dione)‐1, 3‐diyl] (PBDTS‐TPD) with a low‐lying highest occupied molecular orbital level and an acceptor polymer poly[[ N, N′ ‐bis(2‐octyldodecyl)‐naphthalene‐1, 4, 5, 8‐bis(dicarboximide)‐2, 6‐diyl]‐ alt ‐thiophene‐2, 5‐diyl] (PNDI‐T) with a high‐lying lowest unoccupied molecular orbital level is used, realizing high‐performance all‐PSCs with simultaneously high V oc of 1.1 V and high PCE of 8.0%, and surpassing the performance of the corresponding PC71 BM‐based PSCs. The PBDTS‐TPD:PNDI‐T all‐PSCs achieve a maximum internal quantum efficiency of 95% at 450 nm, which reveals that almost all the absorbed photons can be converted into free charges and collected by electrodes. This work demonstrates the advantages of all‐PSCs by incorporating proper donor and acceptor polymers to boost both V oc and PCEs. Abstract : High‐performance all‐polymer solar cells with high V oc of 1.1 V and PCE of 8.0% are realized by incorporating a pair of the donor polymer poly[4, 8‐bis(5‐(2‐octylthio)thiophen‐2‐yl)benzo[1, 2‐ b :4, 5‐ b ′]dithiophene‐2, 6‐diyl‐ alt ‐(5‐(2‐ethylhexyl)‐4 H ‐thieno[3, 4‐ c ]pyrrole‐4, 6(5 H )‐dione)‐1, 3‐diyl] and acceptor polymer poly[[ N, N ′‐bis(2‐octyldodecyl)‐naphthalene‐1, 4, 5, 8‐bis(dicarboximide)‐2, 6‐diyl]‐ alt ‐thiophene‐2, 5‐diyl]. The simultaneously high V oc and power conversion efficiency stem from the low photon energy loss and high internal quantum efficiency near unity.